Uji Fitokimia Ekstrak Daun Telang (Clitoria Ternate L.) Menggunakan Metode Tabung (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2025)
Butterfly pea (Clitoria ternatea L.) is a type of ornamental plant characterized by flowers in shades of purple, blue, pink, and white. Besides being an ornamental plant, butterfly pea is also commonly used in traditional medicine. Several previous studies have confirmed its health benefits. Therefore, it is necessary to conduct phytochemical screening for flavonoids, saponins, and alkaloids using the Wilstater method, foam test, Dragendorff’s reagent, and Wagner's test. This study demonstrates the presence of flavonoid, saponin, and alkaloid compounds in butterfly pea flowers, indicated by positive results in various tests conducted.